Heterogenous Renal Injury Biomarker Production Reveals Human Sepsis-Associated Acute Kidney Injury Subtypes. (October 2019) - Jou-Valencia, Daniela; Koeze, Jacqueline; Popa, Eliane R.; Aslan, Adnan; Zwiers, Peter J.; Molema, Grietje; Zijlstra, Jan G.; van Meurs, Matijs; Moser, Jill
Abstract : Objectives: To identify mechanisms associated with sepsis-acute kidney injury based on the expression levels of renal injury biomarkers, neutrophil gelatinase–associated lipocalin, and kidney injury molecule-1 in renal biopsies which may allow the identification of sepsis-acute kidney injury patient subtypes. Design: Prospective, clinical laboratory study using "warm" human postmortem sepsis-acute kidney injury kidney biopsies. Setting: Research laboratory at university teaching hospital. Subjects: Adult patients who died of sepsis in the ICU and control patients undergoing tumor nephrectomy. Measurements and Main Results: Reverse transcription quantitative polymerase chain reaction and immunohistochemical staining were used to quantify messenger RNA and protein expression levels of neutrophil gelatinase–associated lipocalin and kidney injury molecule-1 in the kidney of sepsis-acute kidney injury patients and control subjects. Morphometric analysis was used to quantify renal and glomerular neutrophil gelatinase–associated lipocalin and kidney injury molecule-1 protein levels. Neutrophil gelatinase–associated lipocalin and kidney injury molecule-1 messenger RNA and protein levels were increased in kidneys of sepsis-acute kidney injury patients compared with control kidney tissue. Neutrophil gelatinase–associated lipocalin was localized in the distal tubules, collecting ducts, the adventitia of the renal arterioles, and in the glomerular tufts of renal biopsies from sepsis-acute kidney injury patients. In contrast, kidney injury molecule-1 was localized at the brush border of the proximal tubules. There was no correlation between neutrophil gelatinase–associated lipocalin and kidney injury molecule-1 levels. Furthermore, renal neutrophil gelatinase–associated lipocalin and kidney injury molecule-1 levels were not associated with the extent of renal injury, the severity of critical illness, or serum creatinine levels at either ICU admission or day of expiration. By laser microdissecting glomeruli, followed by reverse transcription quantitative polymerase chain reaction, we identified heterogenous glomerular neutrophil gelatinase–associated lipocalin production in the kidney of sepsis-acute kidney injury patients. Conclusion: We found differences in the expression of neutrophil gelatinase–associated lipocalin and kidney injury molecule-1 in patients with the same syndrome "sepsis-acute kidney injury" meaning there is no single pathway leading to sepsis-acute kidney injury. This underscores the beliefs that there are many/different pathophysiological pathways that can cause sepsis-acute kidney injury. Hence, patients with criteria that meet the definitions of both acute kidney injury and sepsis can be divided into subtypes based on pathophysiological features. Abstract : Supplemental Digital Content is available in the text.